2016
DOI: 10.1016/j.actao.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Competition can lead to unexpected patterns in tropical ant communities

Abstract: a b s t r a c tEcological communities are structured by competitive, predatory, mutualistic and parasitic interactions combined with chance events. Separating deterministic from stochastic processes is possible, but finding statistical evidence for specific biological interactions is challenging. We attempt to solve this problem for ant communities nesting in epiphytic bird's nest ferns (Asplenium nidus) in Borneo's lowland rainforest. By recording the frequencies with which each and every single ant species o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 63 publications
1
19
1
Order By: Relevance
“…Although supporting evidence is not unequivocal (Terborgh 2015, Ellwood et al 2016, Gainsbury and Meiri 2017, LaManna et al 2017), local dynamics in the tropics could exclude different consumers in different habitat patches, resulting in more specialized and less similar consumer communities across patches. Our results show that consumers segregated their dietary niches more in more constant environments (less consumer overlap) (Figure 3).…”
Section: Discussionmentioning
confidence: 97%
“…Although supporting evidence is not unequivocal (Terborgh 2015, Ellwood et al 2016, Gainsbury and Meiri 2017, LaManna et al 2017), local dynamics in the tropics could exclude different consumers in different habitat patches, resulting in more specialized and less similar consumer communities across patches. Our results show that consumers segregated their dietary niches more in more constant environments (less consumer overlap) (Figure 3).…”
Section: Discussionmentioning
confidence: 97%
“…The proximate mechanisms underlying these varying tendencies of different Tetradonia species to co-occur in a given colony remain unknown. In general, co-occurrence patterns can be governed by various factors including interspecific competition [52], environmental filtering due to abiotic factors [53], host-encounter- and compatibility-filtering in the case of symbioses [18,54], as well as stochastic processes [55,56]. Studying potential proximate mechanisms in the future, such as the host-searching behavior of different myrmecophiles (encounter filtering; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While unexpected, these low levels of competition echo the remarkably low levels of competition observed between other invertebrates in bird's nest ferns, such as arthropod decomposers (Ellwood et al., ) and ant communities (Ellwood et al., ; Fayle, Eggleton, Manica, Yusah, & Foster, ). These previous studies concluded that competition must be less important in the harsh physical conditions of the high canopy (Ellwood et al., , ). However, we should continue to look at other biological explanations, such as resource partitioning, complementarity, or predation pressure.…”
Section: Discussionmentioning
confidence: 78%
“…Again the C ‐scores were not significant in terms of species co‐occurrence. Moreover, in the low canopy the observed C ‐score was lower than that of simulated random communities ( C obs = 3.97, C sim = 7.91, p = .38), suggesting species aggregation rather than segregation (Ellwood, Blüthgen, Fayle, Foster, & Menzel, ). In the high canopy, the observed C ‐score was higher than that of the random simulations, suggesting species segregation, although this result was not significant ( C obs = 8.05, C sim = 7.81, p = .085).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation